USING THE PHOTOVOICE METHODOLOGY TO INCREASE ENGAGEMENT AND SHARPEN STUDENTS' ANALYTICAL SKILLS REGARDING CULTURES, LIFESTYLES, AND MARKETS INTERNATIONALLY. Issue 2 (4th May 2018) - Kelly, Kathleen; Lee, Seung Hwan (Mark); Bowen Ray, Heather; Kandaurova, Maria
Abstract : Barriers to cross-cultural instruction challenge even experienced educators and their students. To increase cross-cultural competence and bridge learning gaps, professors in two countries adapted the Photovoice methodology to develop shared visual vocabularies with students and unearth hidden assumptions. Results from an anonymous evaluation showed that the assignment using the Photovoice method led to higher interest, enthusiasm, and engagement. As students become active participants of image gathering and interpretation, learning arises from increased visual literacy and exploration of cultural bias. Students can use lessons to improve business practices and societal conditions. The appendices include assessment results, sample instructions, and sample student slides.